2013
DOI: 10.1007/s10903-013-9861-1
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Distress in Afghan Refugees: A Mixed-Method Systematic Review

Abstract: Mental health problems disproportionately affect Afghan refugees and asylum seekers who continue to seek international protection with prolonged exposure to war. We performed a systematic review aimed at synthesizing peer-reviewed literature pertaining to mental health problems among Afghans resettled in industrialized nations. We used five databases to identify studies published between 1979 and 2013 that provided data on distress levels, and subjective experiences with distress. Seventeen studies met our inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
116
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 127 publications
(131 citation statements)
references
References 89 publications
10
116
0
2
Order By: Relevance
“…Previous work on refugees and Afghan refugees has found this same pattern [21,22]. [34], found that for Southeast Asians, 10 years after relocating to Canada, low English ability was associated with depression for women but not men.…”
Section: Hypothesis 1: Women Will Report Higher Levels Of Distress Thsupporting
confidence: 52%
“…Previous work on refugees and Afghan refugees has found this same pattern [21,22]. [34], found that for Southeast Asians, 10 years after relocating to Canada, low English ability was associated with depression for women but not men.…”
Section: Hypothesis 1: Women Will Report Higher Levels Of Distress Thsupporting
confidence: 52%
“…CA CBT has been evaluated for various ethnic groups but not for Afghan refugees (Hinton et al, 2005, 2009; Jalal et al, 2017), and to our knowledge this is the first treatment study with a Farsi-speaking refugee sample outside Afghanistan. Due to specific cultural barriers in the utilization of psychotherapy (Alemi et al, 2016; Yaser et al, 2016) and the high comorbidity of PTSD with other trauma-related disorders (Alemi et al, 2014) in refugees, CA CBT is conceptualized as a low-threshold transdiagnostic treatment programme.…”
Section: Discussionmentioning
confidence: 99%
“…Our measure of discrimination captured the degree of unfair treatment and marginalization that Afghans perceive, which is concerning given that such acts may further hinder opportunities in social and economic spheres, already known to play a significant role in determining the mental health of Afghan refugees [5]. Importantly, perceived discrimination has a stronger mental health impact on individuals with higher pre-resettlement traumatic experiences in our sample (confirming our third hypothesis), an interplay of variables that is largely understudied in previous research, but here, speaking directly for the vulnerability of this population.…”
Section: Discussionmentioning
confidence: 99%
“…Research on the mental health of Afghans [5], and of many other refugee nationalities has focused on the influences of pre-migration traumas [6] and post-resettlement factors such as ethnic ties, social support, socio-economic and cultural adjustment difficulties, and difficulty with immigration officials [7][8][9].While not a central focus of this line of research, several studies assess the impact of perceived discrimination on refugee health and mental health [10][11].…”
Section: Introductionmentioning
confidence: 99%